2019
DOI: 10.1186/s12909-019-1529-7
|View full text |Cite
|
Sign up to set email alerts
|

The art of note taking with mobile devices in medical education

Abstract: Background Students use mobile devices extensively in their everyday life, and the new technology is adopted in study usage. Since 2013, the University of Helsinki has given new medical and dental students iPads for study use. Simultaneously, an action research project on mobile learning started focusing on these students’ mobile device usage throughout their study years. Note taking is crucial in academic studies, but the research evidence in this area is scarce. The aims of this study were to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 28 publications
3
35
0
Order By: Relevance
“…However, our results were consistent with previous research ndings (1,3,15). Both previous research literature and our own previous research on the rst cohort of medical students reported challenges in incorporating devices into clinical settings (13,17,18,19). For students, this was problematic because they were accustomed and pro cient in using mobile devices in the biomedical science courses in their rst two study years (19), and it was in the clinical setting that the importance of online information sources increased as they participated in patient care and needed immediate access to e.g.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, our results were consistent with previous research ndings (1,3,15). Both previous research literature and our own previous research on the rst cohort of medical students reported challenges in incorporating devices into clinical settings (13,17,18,19). For students, this was problematic because they were accustomed and pro cient in using mobile devices in the biomedical science courses in their rst two study years (19), and it was in the clinical setting that the importance of online information sources increased as they participated in patient care and needed immediate access to e.g.…”
Section: Discussionsupporting
confidence: 92%
“…An action research project has followed medical and dental students' use of iPads since then, collecting data on all new student cohorts and followed their mobile device use in both their pre-clinical and clinical courses (18). Therefore, an opportunity presented itself to explore the student cohorts' device use both vertically, following the development of a cohort during their study years (19), as well as horizontally comparing the device use of different student cohorts at certain stages of their studies. Our search of the literature has not discovered a similar study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another controversial aspect is that students have information about patients outside the healthcare centre. It is a problem that partially arises due to constant technological advances, which have favoured the storage of information and images in mobile devices such as phones, tablets, USB flash drives or laptops among the students themselves [ 58 ]. This practice poses a challenge to professionalism [ 59 ] and involves concerns related to both the privacy of the patient and consent to the availability of such data [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9] Studies have also demonstrated the beneficial effects of iPads and mobile application integration in the clinical learning environment for formative activities such as note and order writing, radiographic interpretations, and learner assessment and feedback. [17][18][19] Our first pass at technology integration into group learning sessions within a clinical course was met with mixed results. As with many educational interventions, a "one size fits all" approach does not equate with success among learners who thrive with varied learning styles.…”
Section: Discussionmentioning
confidence: 99%